Penerapan Peta Konsep (Concept Mapping) Untuk Meningkatkan Aktivitas Dan Hasil Belajar Peserta Didik Kelas VII H SMPN 2 Kauman - Yuni Kartikasari; Fauzatul Ma’rufah Rohmanurmeta; Sudali (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
The objectives of this study were 1) to increase students' activities during the learning process on the material of nonfiction fiction books through the use of concept map learning strategies and 2) to determine the use of concept map learning strategies in an effort to increase students' understanding of material on fiction and nonfiction books. The subjects in this study were students of class VII H SMP Negeri 2 Kauman totaling 30 students. The research was conducted in March 2023. The method used in this research is Classroom Action Research for a total of three cycles. Data collection techniques in this study were observation, documentation, and interviews. The results of data analysis showed that the use of concept map learning strategies succeeded in achieving the desired learning completeness. Learning activities and student learning outcomes increased starting from cycle 1 with a percentage of 71.42% and 73.33%, cycle 2 81.43% and 80%, cycle 3 90.95% and 93.33%. This study shows that the use of concept maps has a positive effect on students and the results of this study can also be used as input for teachers in determining the right learning strategy to improve the expected quality of learning. Keyword: Concept Maping; Classroom Action Research; Fiction and Nonfiction Books.